The evolution of the securities market and modern problems of control of its participants - M. V. Anashkina (Вестник университета)
The purpose of the study is to determine the nature of the impact of digitalization of the domestic securities market on the development of the securities market and the presence of unfair practices on it, in particular, insider trading and manipulation. In the context of the development of technologies and their mass introduction into the financial system, in addition to positive effects, new problems arise related to the control and regulation of its individual elements. Thus, the digitalization of the securities market infrastructure requires the development of a new system of control over compliance with legislation in the field of countering unfair practices. It is necessary to develop new forms and methods of identification and control that meet the level of technologies being implemented. The subject of the study is changes in the securities market and the system of countering unfair practices in the process of its development. The article discusses the main stages of the development of the securities market. Methods of analysis, synthesis and systematisation of data were used. The main problems of countering insider trading and manipulation arising in connection with the introduction of new forms of functioning of the securities market are identified. The scientific significance of the study is to identify the main problems associated with the inconsistency of the existing system for identifying and controlling unfair practices and the current level of development of the securities market infrastructure.